Optimizing the dielectric energy storage performance in P(VDF-HFP) nanocomposite by modulating the diameter of PZT nanofibers prepared via electrospinning. (10th November 2019) - Zhang, Yangyang; Liu, Xiaoru; Yu, Jinyao; Fan, Mingzhi; Ji, Xumin; Sun, Binzhou; Hu, Penghao
Abstract: Polymer-based dielectric nanocomposites are excellent in developing dielectric energy storage devices, and the one-dimensional shape has been considered as a superior morphology for the ceramic nanofillers in dielectric nanocomposite. In the present work, a series of PbZr0.52 Ti0.48 O3 nanofibers (PZT-NF) were prepared via electrospinning. Three different diameter distributions of 500–600 nm, 300–400 nm and around 100 nm were obtained by adjusting the parameters in the electrospinning process, respectively. The nanocomposite films of PZT-NF/P(VDF-HFP) contained with different diameter nanofibers were prepared. The dielectric properties of the nanocomposites were comparatively investigated and the one with the thinnest nanofibers exhibits the best performances. The increasing dielectric permittivity with nanofiber diameter decrease is in accord with effective medium theory and the enhanced breakdown strength is well demonstrated by phase-field simulation. With larger dielectric displacement and breakdown strength, the nanocomposite loaded 3 vol% thinnest nanofibers represents maximal energy density of 12.58 J/cm 3 at 470 kV/mm. The strategy of modulating nanofiber diameter in electrospinning has great potential in further enhancing energy density in dielectric nanocomposites.